Peramalan Nilai Tukar Petani Provinsi Sulawesi Barat dengan Metode Autoregressive Integrated Moving Average - Adhitya Kukuh Pradhana; Fajrin Achmad Rizki; Nafisa Kalyca Candrayani; Felda Nayla Seftiandri; Denti Brina Azalia; Fajar Novianto Alfitrah; Romanus Yoseph Kun Haribowo Purnomosidi (Business and Economic Publication, 2026)
This study examines forecasting the Farmer's Exchange Rate (NTP) of West Sulawesi Province as an indicator of farmer welfare. Its urgency is grounded in historical volatility, where the NTP fluctuated between 100.36 in July 2022 and 158.28 in December 2024. Using monthly time-series data from January 2019 to March 2026, the analysis applies the Autoregressive Integrated Moving Average (ARIMA) approach. The Augmented Dickey-Fuller test confirms stationarity at the first difference with a p-value of 0.0000. ARIMA (3,1,1) was selected as the optimal model due to having the lowest AIC (5.372010) and SC (5.486165) values. Projections indicate a gradual NTP increase from 121.96 in April 2026 to 128.45 in December 2027. These findings provide an empirical foundation for the local government to formulate preventive policies, specifically input price stabilization and optimized subsidy distribution, to protect farmers purchasing power and long-term farmer welfare.